Business Ethics in the Context of Contemporary Transitions - Lamoureux, Dominique (International Transitions, 2024)
I would like to first commend—perhaps with a wink—the courage of the organizers of this roundtable for inviting me. Indeed, in the presence of esteemed academics and experts, I am but a practitioner who, for the past fifteen years, has endeavored to implement an ethical approach within a company, specifically one in the field of defense and security.